The Art of Derivation: Noun-to-Verb Transformations in Student-Written Sentences - Andini, Citra; Bochari, Siska; Marhum, Muchtar; Darmawan (Universitas Negeri Semarang, 2025)
The study investigates the use of affixes in the derivation process from nouns to verbs in sentences produced by EFL students at Tadulako University. This research employed a descriptive quantitative method, with data collected through written tests and questionnaires from 136 fifth-semester students. The data were analyzed using frequency distribution and descriptive statistics. From the written test, a total of 1.370 affixation errors were identified across seven targeted affixes. The prefix de- had the highest number of errors, accounting for 25% of the total. The questionnaire consisted of 50 items and was designed to measure five key variables: semantic clarity, parsing ability, affix frequency, productivity, and pars ability. The responses indicated that 78% of students found affixation confusing due to a lack of semantic transparency, while 65% admitted difficulty in segmenting complex words into base and affix. The reliability test of the questionnaire showed a high Cronbach's Alpha score of 0.988, confirming its internal consistency. The findings revealed that the prefix de- was the most difficult affix for students, with the highest error rate in the noun-to-verb derivation process. Several factors influenced students' difficulties, including semantic aspects, affix frequency, the ability to analyze word structure, affix productivity, and the ease of breaking words into their morphemes. This study highlights the importance of enhancing morphological awareness among EFL students, particularly in applying the derivational process as part of more effective English language learning. This recommendation is based on the observation that students’ limited familiarity with certain affixes, combined with insufficient explicit instruction in morphology, directly impacts their writing proficiency. Therefore, integrating morphological instruction into ELT—through focused affix exercises, contextual application, and parsing training—can significantly enhance students’ vocabulary growth, grammatical accuracy, and confidence in academic writing.